Kitab Kuning dan Pesantren: Peran MA Baitussalam Melestarikan Warisan Intelektual - Hasan, Ismail; Anshory, Isa (Lembaga Yasin AlSys, 2024)
Kitab kuning viewed as theory and values contributor that followed al-Quran and Hadis Nabi as a background. In pesantren world, kitab kuning position are very strategic because it used as text book, references, and curriculum within pesantren education system. Aside from being religion procedure guideline, kitab kuning also functioned as universalreferences on responding every life challenge among pesantren people. This writing presents the results of research on the tradition of reading